Measuring Event Marketing - Harsányi, Dávid (Marketing & Menedzsment, 2019)
The paper presents a comprehensive introduction of event marketing measurement techniques from both academic and practitioner points of view. After defining “event marketing,” its possible goals are summarized and analyzed. Based on these findings, an overall review is presented on measuring possibilities and techniques. The research uses mainly secondary data but also uses in-depth interviews. The paper is based on international material, but also deals with the Hungarian situation.